2018
DOI: 10.5194/bg-2018-484
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of dry and wet Saharan dust deposition in the tropical North Atlantic Ocean

Abstract: <p><strong>Abstract.</strong> Incubation experiments comprising Saharan dust additions were conducted in the tropical North Atlantic Ocean along an east-west transect at 12° N to study the phytoplankton response to nutrient release in oligotrophic seawater conditions. Experiments were performed at three stations (M1, M3, M4), mimicking wet and dry deposition of low and high amounts of Saharan dust deposition from two different dust sources (paleo-lake and sand dune). Dust particle sizes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 56 publications
(94 reference statements)
0
20
0
Order By: Relevance
“…This may stimulate phytoplankton production, which in turn impacts atmospheric CO 2 levels (Guieu et al, ; Jickells et al, ; Mills et al, ; Pabortsava et al, ). Bottle‐incubation experiments with Saharan dust additions along the same transect as in the present study have shown that Saharan dust indeed has the potential to deliver macronutrients and micronutrients (e.g., phosphate, silica, and dissolved iron) if exposed to acidic conditions before deposition (Korte et al, ). Not surprisingly, the concentration of nutrients released is in turn related to the amount of dust deposited, highlighting the importance for accurate dust flux measurements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may stimulate phytoplankton production, which in turn impacts atmospheric CO 2 levels (Guieu et al, ; Jickells et al, ; Mills et al, ; Pabortsava et al, ). Bottle‐incubation experiments with Saharan dust additions along the same transect as in the present study have shown that Saharan dust indeed has the potential to deliver macronutrients and micronutrients (e.g., phosphate, silica, and dissolved iron) if exposed to acidic conditions before deposition (Korte et al, ). Not surprisingly, the concentration of nutrients released is in turn related to the amount of dust deposited, highlighting the importance for accurate dust flux measurements.…”
Section: Resultsmentioning
confidence: 99%
“…This may lead to higher solubility of iron and other nutrients in wet deposition (Spokes et al, ). In contrast, a study by Korte et al () suggests that dry‐deposited dust has a much lower nutrient bioavailability. Also, since satellite instruments cannot detect wet dust deposition below the clouds, a multidisciplinary approach combining in situ observations and satellite remote sensing with model simulations should provide a better understanding of processes involved in dust transport and deposition type and help to constrain the biogeochemical impact of dust deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Dust has been assumed to be the dominant source of these nutrients to the TAO year round (10,15); however, the impact of dust on marine productivity is debated. In fact, a recent study (19) showed that dust has to be extensively acidified to supply SP to seawater, suggesting that other aerosol sources may be more important for providing soluble nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…In terrestrial environments, the residence time of P in soil is longer, facilitating the transformation of insoluble P into more bioavailable forms (9). African dust is thought to be the largest contributor of P to the Amazon and TAO (15), but its solubility is low (16)(17)(18)(19)(20). While P in dust can be transformed into more soluble forms via reactions with acids (20,21), the importance of this process during transport is debated (19,22,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation